2014
DOI: 10.1002/prca.201400011
|View full text |Cite
|
Sign up to set email alerts
|

Surviving the infarct: A profile of cardiac myosin binding protein‐C pathogenicity, diagnostic utility, and proteomics in the ischemic myocardium

Abstract: Summary Cardiac myosin binding protein-C (cMyBP-C) is a regulatory protein of the contractile apparatus within the cardiac sarcomere. Ischemic injury to the heart during myocardial infarction (MI) results in the cleavage of cMyBP-C in a phosphorylation-dependent manner and release of an N-terminal fragment (C0C1f) into the circulation. C0C1f has been shown to be pathogenic within cardiac tissue, leading to the development of heart failure (HF). Based on its high levels and early release into the circulation po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 66 publications
(123 reference statements)
1
17
0
Order By: Relevance
“…HMBG1) are released passively into the circulation during the early phase of cardiac injury. In contrast, C0C1f is actively released early upon cardiac injury by a calpain-dependent cleavage and can be detected in blood within 30 min of MI [12]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HMBG1) are released passively into the circulation during the early phase of cardiac injury. In contrast, C0C1f is actively released early upon cardiac injury by a calpain-dependent cleavage and can be detected in blood within 30 min of MI [12]. …”
Section: Discussionmentioning
confidence: 99%
“…The fact that upon MI, C0C1f is released into the circulation prior to cardiac troponins suggests that it may contribute to the initial sterile inflammation [9, 11, 12]. The mechanism of C0C1f release has been studied extensively, showing a correlation between dephosphorylation of cMyBP-C and its µ-calpain-dependent degradation [9].…”
Section: Introductionmentioning
confidence: 99%
“…74 Abundant examples in the literature are available, including a special issue on cardiovascular disease that focused on clinical and translational proteomics. [75][76][77][78][79][80][81][82][83][84][85][86][87] One specific example is activity-based protein profiling with proteomic techniques, which is currently being used to annotate the enzymatic proteome and uses chemical probes that target large groups of enzymes that have similar active-site features. 88 Contributing to the posttranscriptional complexity of the proteome are alternative splicing and isoform variants, often with extensive peptide redundancies, that are not easily addressed by standard rules of parsimony when acquired in the context of multidimensional quantitative proteomic studies.…”
Section: The Promise Of Proteomicsmentioning
confidence: 99%
“…However, recent epitope mapping experiments revealed that the C-pro polyclonal antibody preferentially reacts with epitopes in C0 and to a lesser extent with other N-terminal domains of cMyBP-C such as the regulatory M-domain [24]. The significance of the strong antigenic nature of C0 is currently unknown, but the N-terminus of cMyBP-C has been identified in the development of immunogenic myocarditis suggesting that it is especially provocative to immune cells [30, 31]. N-terminal proteolytic cleavage products of cMyBP-C that include C0 and that are released during cardiac stress have also been shown to be cardio-toxic [30, 32].…”
Section: Discussionmentioning
confidence: 99%